2018
DOI: 10.3389/fncom.2018.00034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking and Dynamic Simulation of AZD3293 and Solanezumab Effects Against BACE1 to Treat Alzheimer's Disease

Abstract: The design of novel inhibitors to target BACE1 with reduced cytotoxicity effects is a promising approach to treat Alzheimer's disease (AD). Multiple clinical drugs and antibodies such as AZD3293 and Solanezumab are being tested to investigate their therapeutical potential against AD. The current study explores the binding pattern of AZD3293 and Solanezumab against their target proteins such as β-secretase (BACE1) and mid-region amyloid-beta (Aβ) (PDBIDs: 2ZHV & 4XXD), respectively using molecular docking and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Amino acid residues, D106, K107 and F108 of BACE-1 active site were found to be commonly interacting with DDC2, DDC3 and AZD3293. Similarly, Hassan et al [16] observed strong hydrogen bonding of AZ3293 with K107. In another study, Rajasekhar et al [17] observed that BACE-1 inhibitors interacted with F108 amino acid of BACE-1.…”
Section: Discussionmentioning
confidence: 78%
“…Amino acid residues, D106, K107 and F108 of BACE-1 active site were found to be commonly interacting with DDC2, DDC3 and AZD3293. Similarly, Hassan et al [16] observed strong hydrogen bonding of AZ3293 with K107. In another study, Rajasekhar et al [17] observed that BACE-1 inhibitors interacted with F108 amino acid of BACE-1.…”
Section: Discussionmentioning
confidence: 78%
“…Molecular docking experiment is best approach to study the binding conformation of ligands within the active region of target proteins . To predict the best‐fitted conformational position, the synthesized compounds, 8a–k , were docked against alkaline phosphatase.…”
Section: Resultsmentioning
confidence: 99%
“…A molecular docking experiment is the best approach to study the binding conformation of ligands against target protein [53][54][55] . The binding pocket analysis showed that deltamethrin and permethrin were confined in the active region of a-glucosidase.…”
Section: Binding Pocket and Deltamethrin And Permethrin Binding Conformationsmentioning
confidence: 99%